Jürg Niehans and the Cashless Economy. (October 2017) - Hendrickson, Joshua R.
Information technology has the potential to decrease substantially, if not completely, the demand for base money. This poses a problem for central banks as it seemingly eliminates a role for monetary policy, at least in the traditional sense. Recently, it has become commonplace to consider the role of monetary policy and the determination of the price level without any reference to money. The two predominant methods of analysis in this regard are the New Keynesian framework articulated by Woodford and the fiscal theory of the price level as described in Cochrane. Lost in the literature on "cashless" economies is the work of Jürg Niehans who, driven by the perplexities of the Eurodollar market, considered the role of monetary policy and price-level determination in the context of a neoclassical macroeconomic model. This article contrasts the framework and conclusions of Niehans with the contemporary approaches. It is argued that Niehans successfully anticipated the conclusions of the fiscal theory of the price level. JEL Classification : E52, E63